Motivasi Kunjungan Wisatawan Terhadap Agrowisata Merapi Farma Herbal Di Dusun Sidorejo, Hargobinangun, Pakem, Sleman, D.I. Yogyakarta - , DANIEL RADITYA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Motivation of touring based on many factors like from inside and outside of a tourists. Merapi Farma Herbal is one of tourist acttraction that provide herb tourism at D.I. Yogyakarta. Uniquesly side of herb can become one of plus point to compete around the worldâs tourism competition right now. With all the deeper knowledge about tourstâs motivation visit Merapi Farma Herbal, hopefully this destination can evolve better. This study using a descriptive technic based on quantitative data. The method of survey used in this study. The datas obtained by distributing questionnaire, make an interview, and direct observation at the location. Object of this study is Merapi Farma Herbal. Sources of the datas are primary that come from doccumentation photos and secondary come from books and internet. The result of study showed that motivation of touristâs visit to Merapi Farma Herbal dominantly based on the desire to refresh and renew soul, desire to get healthy which as free from any disease, and getting happiness from any activities at Merapi Farma Herbal. This study found any booster point that the tourist visit Merapi Farma Herbal were because have desire to cured from any disesase, rest from any daily activities, and recover whole physic, soul, and mind thing. In other hand, Puller point that the tourist visit Merapi Farma Herbal were because benefit of jamu godhog as healthy traditional drink, cool environment around the location, and adequate toilet and parking area.